Alcohol induces mitochondrial redox imbalance in alveolar macrophages - Liang, Yan; Harris, Frank L.; Jones, Dean P.; Brown, Lou Ann S. (Free radical biology & medicine, 2013)
Alcohol abuse suppresses the immune responses of alveolar macrophages (AMs) and increases the risk of a respiratory infection via chronic oxidative stress and depletion of critical antioxidants within alveolar cells and the alveolar lining fluid. Although alcohol-induced mitochondrial oxidative stress has been demonstrated, the oxidation of the mitochondrial thioredoxin redox circuit in response to alcohol has not been examined. In vitro ethanol exposure of a mouse AM cell line and AMs from ethanol-fed mice demonstrated NADPH depletion concomitant with oxidation of mitochondrial glutathione and oxidation of the thioredoxin redox circuit system including thioredoxin 2 (Trx2) and thioredoxin 2 reductase (Trx2R). Mitochondrial peroxiredoxins (Prdx's), which are critical for the reduction of the thioredoxin circuit, were irreversibly hyperoxidized to an inactive form. Ethanol also decreased the mRNAs for Trx2, Trx2R, Prdx3, and Prdx5 plus the mitochondrial thiol-disulfide proteins glutaredoxin 2, glutathione reductase, and glutathione peroxidase 2. Thus, the mitochondrial thioredoxin circuit was highly oxidized by ethanol, thereby compromising the mitochondrial antioxidant capacity and ability to detoxify mitochondrial reactive oxygen species. Oxidation of the mitochondrial thioredoxin redox circuit would further compromise the transient oxidation of thiol groups within specific proteins, the basis of redox signaling, and the processes by which cells respond to oxidants. Impaired mitochondria can then jeopardize cellular function of AMs, such as phagocytosis, which may explain the increased risk of respiratory infection in subjects with an alcohol use disorder.